Victimological Analysis of The Impact of Wrongful Arrest in The Pegi Setiawan Case and Its Influence on The Criminal Justice System in Indonesia - Rena Putri Nirwana; Yuliana Yuli Wahyuningsih (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This study aims to examine the victimological impact of the wrongful arrest case involving Pegi Setiawan in the murder of Vina and Eky, as well as its influence on investigative practices and the use of evidence in the criminal justice system in Indonesia. The case drew national attention because it revealed structural weaknesses in law enforcement processes, particularly concerning the haste in naming suspects, the lack of evidence verification, and the suboptimal protection of suspects' rights. This study aims to analyze the forms of victimization experienced by the wrongfully arrested victim, evaluate the factors causing procedural errors in investigations, and identify the implications for the legitimacy of the criminal justice system. Using a juridical-normative approach and case study analysis, this study found that Pegi suffered psychological, social, and economic losses, as well as prolonged stigma due to the mistakes of law enforcement officials. Furthermore, this case demonstrates a discrepancy between the ideal standards of investigation and field practice, including officers' weak objectivity, professionalism, and accountability in assessing evidence. This study concludes that the Pegi Setiawan case reflects the need for deep reforms through strengthening oversight mechanisms, enhancing investigator capacity, and reinforcing.